2019
DOI: 10.1534/g3.119.400223
|View full text |Cite
|
Sign up to set email alerts
|

Humans and Chimpanzees Display Opposite Patterns of Diversity in Arylamine N-Acetyltransferase Genes

Abstract: Among the many genes involved in the metabolism of therapeutic drugs, human arylamine N -acetyltransferases ( NATs ) genes have been extensively studied, due to their medical importance both in pharmacogenetics and disease epidemiology. One member of this small gene family, NAT2 , is established as the locus of the classic human acetylation polymorphism in drug metabolism. Current hypotheses hold that selective processes favoring haplotypes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 116 publications
(184 reference statements)
2
9
0
Order By: Relevance
“…Here, we investigated NAT1 variability in a population sample of the Old World monkey rhesus macaque, also characterizing the possible functional consequences of detected variants. Our results are in accordance with the aforementioned study 60 , indicating high haplotypic diversity (Hd = 0.817) of (MACMU) NAT1 coding region for the specific rhesus macaque population studied, and with 16% of the haplotypes carrying at least one non-synonymous SNV with some functional impact. It appears that, in the rhesus macaque, polymorphic NAT1 alleles may modulate acetylation of arylamine xenobiotics more effectively compared with human, where population frequencies of non-synonymous SNVs in NAT1 coding region are extremely low (typically <1‰, with few exceptions) 104 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Here, we investigated NAT1 variability in a population sample of the Old World monkey rhesus macaque, also characterizing the possible functional consequences of detected variants. Our results are in accordance with the aforementioned study 60 , indicating high haplotypic diversity (Hd = 0.817) of (MACMU) NAT1 coding region for the specific rhesus macaque population studied, and with 16% of the haplotypes carrying at least one non-synonymous SNV with some functional impact. It appears that, in the rhesus macaque, polymorphic NAT1 alleles may modulate acetylation of arylamine xenobiotics more effectively compared with human, where population frequencies of non-synonymous SNVs in NAT1 coding region are extremely low (typically <1‰, with few exceptions) 104 .…”
Section: Discussionsupporting
confidence: 92%
“…paniscus ) compared with human. Genetic diversity was higher for NAT1 in the two Pan species and lower in human, with the opposite pattern observed for the NAT2 gene 60 . Here, we investigated NAT1 variability in a population sample of the Old World monkey rhesus macaque, also characterizing the possible functional consequences of detected variants.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…High-risk alleles existed at least 45,000 years ago in H. sapiens DNA from Ust'-Ishim (Siberia). N-acetyltransferases (NAT1,NAT2) are important for xenobiotic catabolism of modern drugs and ancient carcinogens such as PAHs in smoke from burning wood and tobacco (Zhou et al 2013;Aarts et al 2016;Vangenot et al 2019). Because the NAT variants alter cancer risk from cigarette smoke (Matejcic et al 2015;Sabbagh et al 2018) and red meat (Wang et al 2015), we suggest that NAT variants also modulate toxicity of domestic smoke from biomass burning used for cooking and warmth.…”
Section: Smoke and Cooking: Detoxification By Ahr-cyp And N-acetyltramentioning
confidence: 99%
“…Actually, the idea that Western chimpanzees underwent a substantial reduction in population size has been supported by analysing other parts of the genome. First, studies on both autosomal genes and whole genome sequences [ 44 , 66 , 67 , 70 , 86 88 ] have indicated that Western chimpanzees are generally less diverse than the other Pan sub-species, which sustains the hypothesis of several past bottlenecks in the former [ 44 , 79 ]; second, Western chimpanzees’ genomic diversity has been found to fall within the average observed for Non-African human populations, which show a much lower genetic diversity than African populations (Fig. 1 b of [ 44 ]).…”
Section: Discussionmentioning
confidence: 99%